Self-assessment: A critical competence for Industrial Engineering (2015)
Assess one's own abilities realistically and critically is the key for a continuous adaptation to the changing labor market conditions. The university system must train the future engineers to rate their own performance accurately, reducing biases as self-benevolence. This paper analyzes, with a sample of students of Industrial Engineering, the accuracy of self-assessment in oral presentations, using a scoring rubric. The results of several statistical tests indicate that students are good assessors of others work, but benevolent with their own work. In addition, men evaluate themselves significantly higher than women do. Finally, self-assessment tend to compensate for others assessments, mainly in the case of students considered worse by teachers. These results point to the need of including self-assessment activities in an increasing number to improve students’ performance.